Efektivitas Metode At-Taisir dalam Meningkatkan Hapalan dan Kualitas Pembelajaran Tahfizh Al-Qur’an di Pondok Pesantren Abinnur Al-Islami Kecamatan Panyabungan Utara Kabupaten Mandailing Natal - Hidayat, Taupiq; Erawadi, Erawadi; Nasution, Abdusima (Pusdikra-Publishing.com, 2025)
This study investigates Tahfizh Al-Qur’an learning through the At-Taisir method at Abinnur Al-Islami Islamic Boarding School, Panyabungan Utara, Mandailing Natal. Using a qualitative approach, data were collected through interviews, observations, documentation, and tests, then analyzed by data reduction, presentation, and conclusion drawing. The findings reveal: (1) The learning process follows systematic planning, implementation, and evaluation. Students repeat verses and memorize gradually, ensuring retention. (2) Memorization improvement emphasizes Tajweed, Fashahah for recitation fluency, and reinforcement through writing, oral repetition, prayer recitation, and the Manzil method. (3) The quality of Tahfizh learning improved significantly after applying the At-Taisir method, seen in increased knowledge, skills, and character development. (4) The method’s effectiveness is supported by clear objectives, appropriate strategies, comprehensive planning, adequate facilities, structured programs, efficient implementation, and supervision systems. Overall, the At-Taisir method effectively enhances memorization and the quality of Tahfizh Al-Qur’an learning, contributing to both academic and spiritual development of students.